Effect of breed and season on production and response to infections with gastro-intestinal nematode parasites in sheep in the highlands of Ethiopia - Rege, J.E.O.; Tembely, S.; Mukasa-Mugerwa, E.; Sovani, S.; Anindo, D.O.; Lahlou-Kassi, A.; Nagda, S.M.; Baker, R.L. (Elsevier, 2002)
The effects of breed (Menz and Horro), season (wet and dry), and the breed by season interaction on production and response to naturally acquired gastro-intestinal (GI) nematode parasite infections (predominantly Longistrongylus elongata and Trichostrongylus spp. and a small proportion of Haemonchus contortus) of lambs in the highlands of Ethiopia were investigated. A total of 2395 Menz and 1966 Horro lambs, born from five lambings in the wet season and five lambings in the dry season, were recorded in the study from birth to 12 months of age. These were the progeny of 43 Menz and 41 Horro rams. Horro lambs were significantly (P<0.001) heavier than Menz lambs from birth to 12 months of age and in young lambs this was particularly marked in the wet season. Young Menz lambs born in the wet season had a significantly lower (P<0.001) logarithm-transformed faecal egg count (LFEC) than Horro lambs at 2 and 3 months of age. The Menz lambs had a significantly higher (P>0.001) packed cell volume (PCV) than the Horro lambs at 3 and 12 months of age, possibly indicating a better adaptation of the Menz to a high altitude environment. The Menz lambs had significantly (P<0.001) lower cumulative mortality (37%) to 12 months of age than the Horro (68%), principally due to better adaptation of the Menz to the study environment and not due to resistance to GI nematode parasites. Heritabilities for and genetic correlations among live weight (LWT), PCV and LFEC were estimated. Overall results showed that, in this environment, the Menz are more productive than the Horro.